Hypoalbuminemia in peritoneal dialysis patients - Tze-Wah Kao; Chun-Chun Pan; Shu-Neng Chueh; Hsiu-Lin Hsiao; Jenq-Wen Huang; Kuan-Yu Hung; Kwan-Dun Wu; Tun-Jun Tsai (The Korean Society of Nephrology, 2012)
This study aimed to determine the factors that were associated with hypoalbuminemia in peritoneal dialysis (PD) patients. End-stage renal disease patients who had received PD at the National Taiwan University Hospital for more than three months were included and divided into two groups. Patients who had mean serum albumin levels greater or equal to 3.5 g/dL were allocated to Group 1, while those who had mean serum albumin levels less than 3.5 g/dL were allocated to Group 2. Demographic characteristics, clinical parameters and laboratory data were then compared between the two groups. Logistic regression was also performed to identify the factors that were associated with hypoalbuminemia. There were 359 patients (mean age 54.3 years, male 46.5%) included. Group 2 patients (10.3%) were older (P=0.0536), had lower body mass index (P=0.0008), lower total Kt/V (P=0.0060), and lower levels of hemoglobin (P=0.0268), blood urea nitrogen (P=0.0501), creatinine (P<0.0001), triglyceride (P=0.0014), potassium (P=0.0028), phosphorus (P=0.0036), but higher levels of C-reactive protein (P=0.0194). More Group 2 patients had high or high-average peritoneal equilibration test (PET) (P=0.0199). Using logistic regression, factors that were found to be associated with hypoalbuminemia were total Kt/V (P=0.0015), hemoglobin (P=0.0019), creatinine (P<0.0001), triglyceride (P=0.0060), and potassium (P=0.0126). In conclusion, hypoalbuminemia in our PD patients was associated with total Kt/V as well as levels of hemoglobin, creatinine, triglyceride, and potassium.